Determination of Zinc, Copper, Iron, and Manganese in Different Regions of Lamb Brain - Bakirdere, Sezgin; Kizilkan, Nese; Yaman, Mehmet (Humana Press Inc, 2011)
The levels of zinc, copper, iron, and manganese were measured in the hippocampus, thalamus, gyrus cinguli, hypothalamus, and in the prefrontal, parietal, temporal, and occipital cortexes of lamb brain by flame atomic absorption spectrometry. Standard addition method was also applied to samples and it was observed that there was no matrix interference affecting the determination of elements interested. In the determination of Cu, a slotted tube atom trap was used to improve sensitivity. One-way analysis of variance was used for the statistical evaluation of the results for each element. Limit of detection results for Zn, Cu, Fe, and Mn were found to be 24, 4.5, 60, and 25 ng/mL, respectively. Region-specific differences were found for all elements interested. Mn concentration ranging from 0.29 +/- 0.04 to 0.61 +/- 0.04 mg/kg was found to be the lowest in all brain regions among the all elements interested.
Keywords: Lamb brain; Zinc; Copper; Iron; Manganese